Anticoagulation Management in High Bleeding-Risk ECMO in Adults - De Paulis, Stefano; Cavaliere, Franco (Frontiers in Cardiovascular Medicine, 2022)
Extracorporeal membrane oxygenation (ECMO) is a life-saving therapy that has increasingly been used in recent years for the treatment of severe respiratory failure or cardiogenic shock, in the veno-venous (VV) or veno-arterial (VA) configuration respectively (1). ECMO is a complex procedure not without significant complications including both thrombosis and bleeding. The use of an extracorporeal circuit for cardiopulmonary support exposes blood to nonbiologic, thrombogenic surfaces and for this reason ECMO protocols recommend systemic anticoagulation. The presence of active bleeding or a high bleeding-risk scenario are common occurrence in the typical critically ill, ECMO-candidate patient making the choice of the anticoagulation strategy very challenging.